Crossing Boundaries and Fetishization: Experiences of Sexual Violence for Trans Women of Color - Ussher, Jane M. (Journal of interpersonal violence, 2022)
Transgender (trans) women are at higher risk of sexual violence than cisgender women, with trans women of color reported to be at highest risk. This study examined subjective experiences of sexual violence for 31 trans women of color living in Australia, average age 29 (range 18?54), through in-depth interviews. An additional photovoice activity and follow-up interviews were completed by 19 women. Data were analyzed through thematic analysis and feminist intersectionality theory, identifying the following themes. The first theme, ??A sexually tinged violation of boundaries?: Defining sexual violence,? examined women?s definition of sexual violence, including staring and verbal abuse, nonconsensual touching and sexual assault, in both public and private contexts. The second theme, ??Crossing people?s boundaries?: Sexual harassment in the public domain,? examined the frequent sexual harassment women experienced in their daily lives. This included the subtheme, ?A hostile gaze: Public staring and ?weird looks?? and ?Mockery and transphobic abuse: Verbal abuse is sexual violence.? The third theme, ??Crossing bodily boundaries?: Experiences of sexual assault,? included the subthemes ??Unwanted sexual touch?: Groping and forced sex by strangers,? ?Danger in relationships: Sexual assault and manipulation,? ?Sexual violence in the context of sex work,? and ??We?re turned into something we?re not?: Fetishization and the sexual other.? The poor health outcomes experienced by many trans women are closely associated with their exposure to sexual violence and the social inequities and transphobia to which they are subjected. Trans women of color may experience additional prejudice and discrimination due to the intersection of gender, sexuality, race, and social class. Our research suggests that understanding these intersectionalities is integral in understanding the sexual violence experiences of trans women of color.